A Protease Storm Cleaves a Cell-Cell Adhesion Molecule in Cancer: Multiple Proteases Converge to Regulate PTPmu in Glioma Cells - Phillips-Mason, Polly J.; Craig, Sonya E.L.; Brady-Kalnay, Susann M. (Journal of cellular biochemistry, 2014)
Cleavage of the cell–cell adhesion molecule, PTPµ, occurs in human glioblastoma multiforme brain tumor tissue and glioma cell lines. PTPµ cleavage is linked to increased cell motility and growth factor independent survival of glioma cells in vitro. Previously, PTPµ was shown to be cleaved by furin in the endoplasmic reticulum to generate membrane associated E‐ (extracellular) and P‐ (phosphatase) subunits, and by ADAMs and the gamma secretase complex at the plasma membrane. We also identified the presence of additional extracellular and intracellular PTPµ fragments in brain tumors. We set out to biochemically analyze PTPµ cleavage in cancer cells. We determined that, in addition to the furin‐processed form of PTPµ, a pool of 200 kDa full‐length PTPµ exists at the plasma membrane that is cleaved directly by ADAM to generate a larger shed form of the PTPµ extracellular segment. Notably, in glioma cells, full‐length PTPµ is also subject to calpain cleavage, which generates novel PTPµ fragments not found in other immortalized cells. We also observed glycosylation and phosphorylation differences in the cancer cells. Our data suggest that an additional serine protease also contributes to PTPµ shedding in glioma cells. We hypothesize that a “protease storm” occurs in cancer cells whereby multiple proteases converge to reduce the presence of cell–cell adhesion molecules at the plasma membrane and to generate protein fragments with unique biological functions. As a consequence, the “protease storm” could promote the migration and invasion of tumor cells. J. Cell. Biochem. 115: 1609–1623, 2014. © 2014 Wiley Periodicals, Inc.